Six factors facilitating teachers’ use of research. An experimental factorial survey of educational stakeholders perspectives - Jeune, Nathanael; Juhel, Jacques; Dessus, Philippe; Atal, Ignacio (Frontiers in Education, 2024)
Introduction Teachers’ use of research has been increasingly advocated for in the past few decades, and some research has documented the factors which positively or negatively influence teachers’ use of research. However, the existing research does not give relevant information to prioritize between different ways to facilitate teachers’ use of research. In addition, different professionals working in education may have divergent opinions about such priorities. This study therefore asks what are the factors that most influence teachers’ use of research according to teachers, teacher trainers, educational decision makers and researchers? Methods We conducted a factorial survey experiment on six factors with 100 participants (pilot study) and 340 participants (main study) to identify which factors were perceived as influencing the most teachers’ use of research and to compare respondents’ perceptions according to their main role in education. Results This study shows that support for research use by the institution and instrumental utility of research are the factors that were judged as most impactful. Some categories of respondents had conflicting views about specific factors, for instance researchers perceiving teachers’ involvement in research as less likely to facilitate teachers’ use of research. Conclusion These findings can help decision-makers and teacher-trainers with limited resources to allocate them in a more effective way, while taking into consideration the disagreements across professions in order to resolve possibly arising conflicts.